2009
DOI: 10.1111/j.1460-9568.2009.06673.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomy of grapheme–color synesthesia

Abstract: Grapheme-color synesthetes perceive particular colors when seeing a letter, word or number (grapheme). Functional neuroimaging studies have provided some evidence in favor of a neural basis for this type of synesthesia. Most of these studies have reported extra activations in the fusiform gyrus, which is known to be involved in color, letter and word processing. The present study examined different neuroanatomical features (i.e. cortical thickness, cortical volume and cortical surface area) in a sample of 48 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 55 publications
(146 reference statements)
7
105
0
1
Order By: Relevance
“…We tested for differences between synesthetes and controls in a number of areas reported in previous VBM studies (Jäncke et al, 2009;Weiss and Fink, 2009). We therefore performed a post hoc analysis on the left and right anterior intraparietal sulcus (both hIP1 and hIP2) from the Juelich Histological Atlas (Choi et al, 2006) and bilaterally in the fusiform gyrus; occipital fusiform gyrus, temporal occipital fusiform cortex, temporal fusiform cortex (anterior division), and temporal fusiform cortex (posterior division) from the Harvard-Oxford cortical structural atlas.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tested for differences between synesthetes and controls in a number of areas reported in previous VBM studies (Jäncke et al, 2009;Weiss and Fink, 2009). We therefore performed a post hoc analysis on the left and right anterior intraparietal sulcus (both hIP1 and hIP2) from the Juelich Histological Atlas (Choi et al, 2006) and bilaterally in the fusiform gyrus; occipital fusiform gyrus, temporal occipital fusiform cortex, temporal fusiform cortex (anterior division), and temporal fusiform cortex (posterior division) from the Harvard-Oxford cortical structural atlas.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies found activation (Gray et al, 2006) or increased white matter integrity (Jäncke et al, 2009) in the hippocampal region, but examined only the contrast between synesthetes and nonsynesthetes. In cognitive (neuro)psychology literature, the hippocampus is mostly known for its implication in memory functions, including episodic and declarative memory (Scoville and Milner, 1957;Squire, 1992;Eichenbaum, 2004), but also spatial memory (O'Keefe and Nadel, 1978;Maguire et al, 2000).…”
Section: Associator Grapheme-color Synesthesiamentioning
confidence: 99%
See 2 more Smart Citations
“…These include, for example, studies associating posterior tract reductions in FA with visual and other hallucinations (Ashtari et al, 2007;Fujiwara et al, 2007 (Melero et al, 2013;Hänggi et al, 2008;and Whitaker et al, 2014 respectively). Yet other researchers may have been in a position to find reduced FA but stated a priori they would not to explore this direction within their results (Jäncke et al, 2009). Moreover, at least one functional study of synesthetes found a deactivation of certain areas in response to synesthesia-inducing stimuli (Paulesu et al, 1995).…”
Section: Discussionmentioning
confidence: 97%